The Quantitative Importance of Openness in Development - Wenbiao Cai; B. Ravikumar; Raymond Riezman (Center for Economic Studies and ifo Institute (CESifo), 2013)
This paper deals with a classic development question: how can the process of economic development - transition from stagnation in a traditional technology to industrialization and prosperity with a modern technology - be accelerated? Lewis (1954) and Rostow (1956) argue that the pace of industrialization is limited by the rate of capital formation which in turn is limited by the savings rate of workers close to subsistence. We argue that access to capital goods in the world market can be quantitatively important in speeding up the transition. We develop a parsimonious open-economy model where traditional and modern technologies coexist (a dual economy in the sense of Lewis (1954)). We show that a decline in the world price of capital goods in an open economy increases the rate of capital formation and speeds up the pace of industrialization relative to a closed economy that lacks access to cheaper capital goods. In the long run, the investment rate in the open economy is twice as high as in the closed economy and the per capita income is 23 percent higher.
Keywords: O11; F43; O14; 330; openness; industrialization; capital formation; relative price of investment